2019
DOI: 10.1007/s40120-019-00169-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Markers of Alzheimer’s Disease: Quantitative EEG Approach

Abstract: Currently established and employed biomarkers of Alzheimer's disease (AD) predominantly mirror AD-associated molecular and structural brain changes. While they are necessary for identifying disease-specific neuropathology, they lack a clear and robust relationship with the clinical presentation of dementia; they can be altered in healthy individuals, while they often inadequately mirror the degree of cognitive and functional deficits in affected subjects. There is growing evidence that synaptic loss and dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 137 publications
(149 reference statements)
5
51
0
1
Order By: Relevance
“…However, when compared to the NCs, the VBM analysis demonstrated decreased volumes in the left thalamus and the bilateral hippocampus in the EF but in the right frontal and temporal lobe in the RF group. The qEEG pattern observed in the EF group in our study was similar to the pattern observed for AD in numerous previous qEEG studies, which showed increased power in low frequency bands (delta and theta) and decreased power in high frequency bands (alpha and beta) [25][26][27][28][29][30][31]. A recent study suggested an increase in relative theta power as a first change in patients with AD [25].…”
Section: Discussionsupporting
confidence: 89%
“…However, when compared to the NCs, the VBM analysis demonstrated decreased volumes in the left thalamus and the bilateral hippocampus in the EF but in the right frontal and temporal lobe in the RF group. The qEEG pattern observed in the EF group in our study was similar to the pattern observed for AD in numerous previous qEEG studies, which showed increased power in low frequency bands (delta and theta) and decreased power in high frequency bands (alpha and beta) [25][26][27][28][29][30][31]. A recent study suggested an increase in relative theta power as a first change in patients with AD [25].…”
Section: Discussionsupporting
confidence: 89%
“…The qEEG pattern observed in the EF group in our study was similar to the pattern observed for AD in numerous previous qEEG studies, which showed increased power in low frequency bands (delta and theta) and decreased power in high frequency bands (alpha and beta) [18][19][20][21][22][23][24]. A recent study suggested an increase in relative theta power as a rst change in patients with AD [18].…”
Section: Discussionsupporting
confidence: 89%
“…The qEEG pattern observed in the EF group in our study was similar to the pattern observed for AD in numerous previous qEEG studies, which showed increased power in low frequency bands (delta and theta) and decreased power in high frequency bands (alpha and beta) [25][26][27][28][29][30][31]. A recent study suggested an increase in relative theta power as a rst change in patients with AD [25].…”
Section: Discussionsupporting
confidence: 89%